Infecção por Mycoplasma hyorhinis em casos precoces de pneumonia micoplásmica e comparação entre técnicas diagnósticas - Carlos Eduardo Real Pereira (2014)
Enzootic pneumonia caused by bacteria of the genus Mycoplasma is a disease of great importance in the pig industry. Due to the controversial role of Mycoplasma hyorhinis in this disease, confirmation of the presence of these bacteria, and the identification of their roles, in respiratory disease remains a major challenge. The objectives of this study were to compare different techniques, especially fluorescent in situ hybridization (FISH), for diagnosis of respiratory mycoplasmosis in naturally infected pigs, and to evaluate the presence of M. hyorhinis in early cases of mycoplasmal pneumonia. Ninety M. hyopneumoniae and/or M. hyorhinis infected lung tissue samples were selected based on the mosaic of diagnosis (clinical signs, gross and microscopic lesions and PCR) were used. The average age of animals in group 2 (PCR positive for M. hyorhinis only) was 57.32 days and 116.31 days (P <0.01) for group 1 (PCR positive for M. hyopneumoniae only). These findings suggest that colonization and development of lesions caused by M. hyorhinis occur earlier than those caused by M. hyopneumoniae. Microscopic changes were statistically (P <0.01) more intense in group 1 than in group 2. Using the mosaic of diagnosis as the gold standard, the sensitivity and specificity of FISH for M. hyopneumoniae was 75 and 100%, respectively, and 40 to 73.3% by immunohistochemistry. The sensitivity and specificity of FISH for M. hyorhinis was 76.7 to 100%, respectively. These findings demonstrate that FISH can be a useful tool for diagnosing mycoplasmosis. The presence of viral antigens (PCV2 or influenza A) was detected in 53.3% of the samples in group 2 (M. hyorhinis) and 13.3% of the samples in group 1 (M. hyopneumoniae).